1976
DOI: 10.1111/j.1464-410x.1976.tb06702.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Bladder Tumour Cases Identified During Ten Years' Interviewing of Patients

Abstract: All patients attending the Royal Marsden Hospital with urothelial tumours have their occupational histories taken. About 10% of histories suggest a possibility of past exposure to urinary carcinogens, and on examination 4% indicate definite exposures justifying claims for Prescribed Industrial Disease benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1980
1980
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…The role of occupational exposure to chemicals in the aetiology of bladder cancer has been studied extensively [ 1]. Reviews of this literature have provided estimates of the proportions of bladder tumours which might be attributed to such exposures [ 2–4] and an overview by Doll and Peto noted that ‘Figures of 10% in men and 5% in women ... are not likely to be far out’ [ 5]. The objectives of the present case‐control study were threefold: first, to determine whether occupational exposures remain an important cause of recently diagnosed cases of urothelial cancer; second, to identify occupations for which further assessment or control is necessary; and third, to identify occupations which present unrecognized risks of urothelial tumours.…”
Section: Introductionmentioning
confidence: 99%
“…The role of occupational exposure to chemicals in the aetiology of bladder cancer has been studied extensively [ 1]. Reviews of this literature have provided estimates of the proportions of bladder tumours which might be attributed to such exposures [ 2–4] and an overview by Doll and Peto noted that ‘Figures of 10% in men and 5% in women ... are not likely to be far out’ [ 5]. The objectives of the present case‐control study were threefold: first, to determine whether occupational exposures remain an important cause of recently diagnosed cases of urothelial cancer; second, to identify occupations for which further assessment or control is necessary; and third, to identify occupations which present unrecognized risks of urothelial tumours.…”
Section: Introductionmentioning
confidence: 99%
“…This is well under 1% of the incidence of urothelial cancer (Glashan, 1982). In a detailed study of the occupational histories of urothelial cancer patients at the Royal Marsden Hospital, Davies et al (1976) found that 10% had histories suggesting industrial exposure but only 4% justified claims for PD Benefit. Because of the special interests of this hospital and referral practice this series was inevitably highly selected.…”
mentioning
confidence: 99%
“…Die Beobachtungen wurden in den folgenden Jahrzehnten auch auf andere Indu striezweige ausgeweitet, so daß bestimmte Berufsgruppen mit einem erhöhten Blasentumorrisiko festgestellt werden konn ten. Es handelte sich hierbei im wesentlichen um Arbeiter bestimmter chemischer Industriezweige der Kabel-, Reifen-, Gummi-, Gas-, Leder-und Farbstoffindustrie [20,32,33,42]. Etwa 18% der Harnblasenkarzinome dürften bei Männern durch diese industriellen Karzinogene verursacht werden; für Frauen liegen die Angaben mit 6 % deutlich niedriger [27].…”
Section: äTiologische Faktorenunclassified